Intra – Urban Traffic Characteristics of Ikot Ekpene – An Emerging Urban Centre in Akwa Ibom State, Nigeria - Daniel, Ekong Effiong; Udoh, Joseph; Udo, Reuben K. (Advances in Social Sciences Research Journal, 2017)
In recent years, many municipal authorities in the developing region of the world have been grappling with traffic related challenges such as increasing rates of traffic accidents and traffic confusion along the major urban roads and streets of their municipalities. There are needs for efficient transportation system to enhance safe and smooth movements of people and goods within the municipalities. This cannot be achieved without rational planning decisions and rational planning decisions cannot be attained without the basic understanding of materials. The materials for transportation planning include not only the physical ways and the vehicles with which people and goods move about but also the volume and characteristics of traffic. The knowledge of these essential materials was lacking in Ikot Ekpene – an emerging urban centre in Akwa Ibom State. The aim of the study was to ascertain the volume and characteristics of traffic in the city. Data were generated through the manual traffic count at three (3) traffic cordon points (TCP) carefully determined. The survey was conducted simultaneously at the three traffic cordon points. Traffic data were generated on the different week day during the hours of 8am – 5pm at hourly intervals. A total of 189 field data sheets were completed and returned and used in the analysis. The traffic was categorized under: (i) Pedestrian, (ii) Bicycle, (iii) Motor cycle, (iv) Tricycle, (v) Buses and Cars, (vi) Heavy duty and trucks. The study revealed the dominance of motorcycle in the traffic flow with a total weekly volume of 49292 (69.94%), followed by Buses and cars 14324 (20.32%); Pedestrian 5504 (7.8%); Heavy duty vehicles/trucks 1221 (1.73%); Tricycle 70 (0%); and Bicycle 69(0%). Limiting the operation of commercial motorcyclists, construction of bye-passes, relocation of public and private commercial motor parks and upgrading of the existing urban roads and streets to provide the pedestrian walk ways were recommended.